Peningkatan Pengetahuan dan Praktek Kebersihan Diri saat Menstruasi Siswi Sekolah Menengah Pertama: Increasing Knowledge and Practice of Personal Hygiene when Menstruation among First High School Female Students - Serlie K. A. Littik; ‪Stefanus Pieter Manongga; Enjelita Mariance Ndoen; Juliatri P. D. Ledo; Ramses Victor Elim (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Good personal hygiene is needed by young women, including during menstruation, to prevent problems or diseases in the reproductive organs. However, many young girls do not have sufficient knowledge regarding this issue. The problem of insufficient knowledge and practice of personal hygiene during menstruation was also found in the students of SMP Negeri 1 Amanuban Selatan. This school is located in South Central Timor (TTS) Regency, East Nusa Tenggara (NTT) Province. This service activity aims to increase the knowledge and practice of personal hygiene for young women during menstruation at SMP Negeri 1 Amanuban Selatan, TTS Regency, NTT. Activities included counseling, discussions, and demonstrations on personal hygiene during menstruation, distribution of personal hygiene kits and sanitary napkins to students, and initiation of the formation of Adolescent Health Cadre groups with teachers as mentors. The results of the service activities showed an increase in knowledge by 50% after counseling and a strong commitment from the students of SMP Negeri 1 Amanuban Selatan to practice personal hygiene during menstruation properly and correctly, and the willingness of teachers to guide and assist groups of adolescent health cadres formed after service activities. The active participation of students and teachers in youth health cadre groups is very important in ensuring the sustainability of the results of community service activities.